Identification of key drivers of the microbial shikimic acid pathway during different materials composting. (September 2022) - Zhao, Li; Zhao, Yue; Zhang, Wenshuai; Wu, Junqiu; Chen, Xiaomeng; Jia, Liming; Zhao, Ran; Wei, Zimin
Graphical abstract: Highlights: The key factors affecting shikimic acid (SA) pathway were identified. The key influencing factors of each metabolite were obviously different. Only the SA content in lawn waste could be affected by physicochemical factors. The more complex environment, the more factors that restrict protocatechuic acid. A new direction for improving SA metabolic intensity during composting. Abstract: Metabolites of shikimic acid (SA) pathway can be used as humic substance (HS) precursors. Due to the complexity of SA anabolism, there were few studies on SA pathway during composting. The aim of this study was to identify the key drivers of SA pathway during different materials composting. During composting, the SA, protocatechuic acid (PA) and gallic acid (GA) decreased by 57.09%, 72.27% and 54.04% on average, respectively. The structural equation model showed that SA had key driving factors (organic matter and pH) during lawn waste composting. In addition, the complexity of material structure was the main factor affecting PA driving factors. The factors and degree of influence on GA varied with different materials. Accordingly, this study provided theoretical support for the improvement of SA metabolic intensity by single material and mixed material composting, and further provided a new direction for future HS research.